2014
DOI: 10.3389/fnbeh.2014.00312
|View full text |Cite
|
Sign up to set email alerts
|

The GPCR membrane receptor, DopEcR, mediates the actions of both dopamine and ecdysone to control sex pheromone perception in an insect

Abstract: Olfactory information mediating sexual behavior is crucial for reproduction in many animals, including insects. In male moths, the macroglomerular complex (MGC) of the primary olfactory center, the antennal lobe (AL) is specialized in the treatment of information on the female-emitted sex pheromone. Evidence is accumulating that modulation of behavioral pheromone responses occurs through neuronal plasticity via the action of hormones and/or catecholamines. We recently showed that a G-protein-coupled receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Lastly the delay of response following either pre-exposure, clothianidin treatment or the combination of the two was very short, indicating that the tuning and processing of the sex pheromone components within the AL occurred very rapidly for these treated males. A similar effect (high percentage and fast response) was obtained after dopamine treatments [45]. These results further confirm that behavioural responses of naive sexually mature A .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lastly the delay of response following either pre-exposure, clothianidin treatment or the combination of the two was very short, indicating that the tuning and processing of the sex pheromone components within the AL occurred very rapidly for these treated males. A similar effect (high percentage and fast response) was obtained after dopamine treatments [45]. These results further confirm that behavioural responses of naive sexually mature A .…”
Section: Discussionsupporting
confidence: 84%
“…e . injections of JH mimetics or ecdysone [29, 30, 38], at the behavioural level by the application of dopamine [45] and at the neuronal level, without behavioural effect, by application of octopamine [36]. In addition to the effects on immature males, we show here that pre-exposure of sexually mature males still enhances their behavioural pheromone response, reaching very high levels (more than 80% responses).…”
Section: Discussionmentioning
confidence: 81%
“…It is also possible that the modulation of AL neuron sensitivity is caused by increased dopamine release, which has been shown to be caused by clothianidin treatments in the rat brain [40]. Even though nothing is known about clothianidin effects on dopamine release in insects so far, the recently observed role of the dopamine/steroid receptor DopEcR in regulating the sensitivity of pheromone-responding AL neurons [28] would allow this type of modulation. Numerous studies have shown a negative effect of neonicotinoid insecticides on cognitive processes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several other genes that relate to reproduction in moths also have been determined by using RNAi, including the DopEcR that relates to sex pheromone response in Agrotis ipsilon [25,99], olfactory receptor in L. dispar [100] and S. litura [34], PBAN [27,36] and PBAN-R [101,102] in many moths that relate to the regulation of sex pheromone biosynthesis, and the FATP and GPAT in B. mori that relate to bombykol biosynthesis [103]. …”
Section: Use Of Rnai For Gene Function Analysis In Mothsmentioning
confidence: 99%